Inhibition of 4-aminopyridine-induced seizures in mice by a novel 3-substituted 1,4-benzodiazepine - N. Ya. Golovenko; V. B. Larionov; A. S. Reder; I. P. Valivodz' (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Some of highly effective antiepileptic substances share the polymodal pharmacological action which determines the possibility of their use for treatment of pathogenetically similar diseases. Inhibitory mediator systems influence for example, suggests the combination in the pharmacological spectrum such actions as antiepileptic, analgesic (antineuropathic) and other actions. The aim of the study was evaluation of anticonvulsant effect of 7-bromo-5-(o-chlorophenyl)-3-propoxy-1,2-dihydro-3H-1,4-benzodiazepin-2-one (propoxazepam) on the model of 4-aminopyridine (4-AP) - induced myoclonic seizures and characterization of its possible participation in modulation of the function of voltage-dependent potassium channels. 4-AP (10.3 mg/kg, subcutaneously) was administered 30 minutes after intraperitoneal administration of propoxazepam different doses (20, 28, 40, 60 and 80 mg/kg) and the time and quantity of myoclonic and tonic convulsions as well as total time to the lethal effect were evaluated. It was found that in this model, propoxazepam possess moderate activity (ED50 = 37,3 ± 7.9 mg/kg) Even at high doses (80 mg/kg) of the test compound, anticonvulsive action did not reach 100%. The quantity of myoclonic seizures and the latency time of their onset have no statistically significant differences in comparison with the data of animals of the control group. On the contrary, the number (and percentage representation) of tonic convulsions in the common seizure episode increased, which is due to the possible inhibitory effect of propoxazepam, which is carried out primarily through GABA-ergic mechanisms.